Liver lobes and cirrhosis: Diagnostic insights from lobar ratios - Kriti Pandey; Debabrata Dash; Raj Kumar Koiri (Gastroenterology & Endoscopy)
Liver cirrhosis is the formation of abnormal nodular structure and fibrosis. Globally it accounts for 4 ​% of all deaths. Alcohol, viral hepatitis, and non-alcoholic fatty liver disease are the most common cause of cirrhosis. Cirrhosis progresses from the compensated stage to the decompensated stage. It is end-stage liver disease. Anatomically, the liver is divided into four lobes, the right lobe, the left lobe, the caudate lobe, and the quadrate lobe. This lobe varies in size and location within the liver, the right lobe being the largest. Cirrhosis primarily causes portal hypertension which has a varying impact on the four lobes. The right lobe undergoes atrophy due to its acentric location from a central vein and the caudate lobe undergoes hypertrophy due to its central location from the central vein. Preferential perfusion occurs in the caudate lobe and there is a decrease in perfusion in the right lobe. The early non-invasive diagnosis of cirrhosis is required for safe and curable treatment of early-stage cirrhosis. The size variability induced by cirrhosis plays a significant role in its diagnosis. Two key ratios for early cirrhosis detection are the caudate-to-right lobe ratio and the right-to-left lobe ratio, with the former being more substantial. The caudate-to-right-lobe ratio (C/RL) is a key morphological marker for evaluating liver changes in cirrhosis. A C/RL ratio above 0.65 suggests the presence of cirrhosis, making it a valuable tool in diagnosing the condition. These measurements are non-invasive, safe, and crucial for early diagnosis of cirrhosis.